FROM THE HISTORY OF TEXTILE AND SEWING IN THE FERGHANA VALLEY - Noila Obobakirovna Khayitboeva (Journals Park Publishing, 2023)
Given article has been analyzed the history of the textile and sewing in the Ferghana Valley in detail with the help of scientific literature and media as well.
Keywords: Ferghana Valley, national crafts, textile, sewing, archaeological research.